Apolipoprotein A1 as a potential biomarker in the ascitic fluid for the differentiation of advanced ovarian cancers. (September 2013) - Hariprasad, Gururao; Hariprasad, Roopa; Kumar, Lalit; Srinivasan, Alagiri; Kola, Srujana; Kaushik, Amit
Abstract Context: Primary ovarian cancer and ovarian metastasis from non-ovarian cancers in advanced stage are closely mimicking conditions whose therapeutics and prognosis are different. Objective: To identify biomarkers that can differentiate the two variants of advanced ovarian cancers. Methods: Gel-based proteomics and antibody-based assays were used to study the differentially expressed proteins in the ascitic fluid of fourteen patients with advanced ovarian cancers. Results: Programmed Cell Death 1-Ligand 2, apolipoprotein A1, apolipoprotein A4 and anti-human fas antibody are differentially expressed proteins. Conclusions: Apolipoprotein A1 with a 61.8 ng/ml cut-off is a potential biomarker with the best differentiating statistical parameters.